Solutions for a quasilinear elliptic equation in Musielak–Sobolev spaces. (December 2015) - Liu, Duchao; Zhao, Peihao
Abstract: Critical point theory is used to show the existence of weak solutions to a quasilinear elliptic differential equation under the functional framework of the Musielak–Sobolev spaces in a bounded smooth domain with Dirichlet boundary condition.